2020
DOI: 10.1021/acs.langmuir.0c01822
|View full text |Cite
|
Sign up to set email alerts
|

Metal (Mn, Fe, Co, Ni, Cu, and Zn) Phthalocyanine-Immobilized Mesoporous Carbon Nitride Materials as Durable Electrode Modifiers for the Oxygen Reduction Reaction

Abstract: In the search for alternative sources to replace fossil fuels, carbon nitride materials can be used in a variety of ways. In the present work, porosity is introduced to the carbon nitride material using mesoporous silica material, MCM-41, as a hard template, and a mesoporous carbon nitride (MCN) material is synthesized. Further, the MCN is modified by immobilizing metal phthalocyanine (MPc, where M = Mn, Fe, Co, Ni, Cu, and Zn). The resulting MPc-incorporated MCN materials (MPc@MCN) were tested for the electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 69 publications
0
34
0
Order By: Relevance
“…The degrees of aggregation depend on various factors, such as solvent, concentration, sidechain substituent, and the coordinated metal. 4 The exploitation of the MPc aggregation and redox mechanism can be beneficial for its applications in the fields of photophysics, 5 photochemistry, 6 materials 7 and catalysis. 8 Transition metal phthalocyanine dual-metal-site catalysts 9 and composite anchoring iron phthalocyanine (FePc)/TiO 2 heterostructure 10 demonstrated good photocatalytic activities for CO reduction or organic contaminant degradation.…”
Section: Introductionmentioning
confidence: 99%
“…The degrees of aggregation depend on various factors, such as solvent, concentration, sidechain substituent, and the coordinated metal. 4 The exploitation of the MPc aggregation and redox mechanism can be beneficial for its applications in the fields of photophysics, 5 photochemistry, 6 materials 7 and catalysis. 8 Transition metal phthalocyanine dual-metal-site catalysts 9 and composite anchoring iron phthalocyanine (FePc)/TiO 2 heterostructure 10 demonstrated good photocatalytic activities for CO reduction or organic contaminant degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Mesoporous carbon nitride (MCN)-immobilized metal phthalocyanine (MPc, M = Co, Cu, Fe, Mn, Ni, and Zn) was studied for the ORR in KOH. 123 The study revealed that FePc@MCN had the best ORR and stability because of the strong N-coordination in the Pc of Fe. Integration of Co-doping levels (0-25%) into conductive Fe 3 O 4 grown epitaxially on single-crystal MgO {100} substrates achieved by molecular-beam epitaxy (MBE) growth (at a background pressure 1 × 10 6 Torr; PARADIGM thin-film growth) formed Co-doped Fe 3 O 4 single-crystal thin films with controlled Co content (i.e., 0, 5, 10 and 25%), high conductivity, and exposed active sites.…”
Section: Ferrite-based Spinel-structured Orr Electrocatalystsmentioning
confidence: 96%
“…Mesoporous carbon nitride (MCN) has been evaluated as a support for both metal (Mn, Fe, Co, Ni, Cu, and Zn) phthalocyanine and Co porphyrin ORR catalysts by Singh et al , The MCN was synthesized by a hard templating method to improve the surface area and conductivity of the support. The highest E 1/2 (∼0.05 V) is exhibited by CoPc@MCN in these reports, with a limiting current density < 1.5 mA/cm 2 and n ∼ 1.64 in 0.1 M HClO 4 with rotation.…”
Section: Introductionmentioning
confidence: 99%